Discrete phase numerical model and experimental study of hybrid nanofluid heat transfer and pressure drop in plate heat exchanger - Bhattad A.; Sarkar J.; Ghosh P. (My University, 2025)
In the present study, numerical as well as experimental investigations have been done on the plate heat exchanger using hybrid nanofluid (Al2O3 + MWCNT/water) at different concentration to investigate its effect on heat transfer and pressure drop characteristics. Discrete phase model has been used for the investigation using CFD software and results have been compared with the experimental result as well as result of the homogenous model. Effects of different operating parameters (nanofluid inlet temperature, flow rate and volume concentration) have been studied on coolant outlet temperature, heat transfer rate, convective and overall heat transfer coefficients, Nusselt number, friction factor, pressure drop, pumping power, effectiveness and performance index. Velocity and temperature profiles have been also studied for base fluid, nanofluid and hybrid nanofluid. By using hybrid nanofluid, heat transfer coefficient enhances by 39.16% (merit) with negligible increase in pumping power of 1.23% (demerit). An enhancement in heat transfer and pressure drop characteristics; and hence on the effectiveness of plate heat exchanger has been observed while using hybrid nanofluids instead of base fluid. © 2017 Elsevier Ltd